Synthesis, characterisation, Hirshfeld surface and in vitro cytotoxicity evaluation of new N-aryl-N `-Alkoxycarbonyl thiocarbamide derivatives - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2020)
Four new compounds N-(4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (1), N-(2, 4-nitrophenyl)-N'-(isobutoxycarbonyl) thiocarbamide (2), N-(4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (3) and N-(2-Chloro- 4-nitrophenyl)-N'-(ethoxycarbonyl) thiocarbamide (4) were prepared and their structures confirmed by using various spectroscopic (FT-IR, UV-Visible, H-1 and C-13 NMR) and single crystal X-ray studies of 1 and 3. The presence of intramolecular (N-H center dot center dot center dot O=C) hydrogen bond in the crystal structure of both the compounds causes planarity of carbonyl thiocarbamide unit and trans orientation of C=O and C=S group. The intermolecular contacts (C-H center dot center dot center dot S, C-H center dot center dot center dot O and N-H center dot center dot center dot S) present in crystal structures have been examined by Hirshfeld surface analysis and their associated 2D fingerprint plots. All the compounds were assessed for their in vitro cytotoxic properties against a panel of seven human cancer cells such as cervical carcinoma (2008, C13*), colorectal (HT29 and HCT116) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Among them, compounds 2 and 4 exhibited better activity than 1 and 3 against all the cell lines tested. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure